2005
DOI: 10.1677/erc.1.00905
|View full text |Cite
|
Sign up to set email alerts
|

The anti-oestrogen ICI 182,780, but not tamoxifen, inhibits the growth of MCF-7 breast cancer cells refractory to long-term oestrogen deprivation through down-regulation of oestrogen receptor and IGF signalling

Abstract: Long-term culture of MCF-7 wild-type (wt) cells in steroid-depleted medium (LTED) results in hypersensitivity to oestradiol (E2) coinciding with elevated levels of ERa and enhanced growth factor signalling. In this study, we aimed to compare the effects of the pure anti-oestrogen ICI 182,780 (ICI) with the competitive anti-oestrogen tamoxifen (TAM) on oestrogen and IGF signalling in these cells. Wt MCF-7 and LTED cells were treated with a log 7 concentration range of E2, TAM or ICI. Effects on cell growth, ERa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 46 publications
3
45
0
1
Order By: Relevance
“…The probability of recovery of a particular gene under different selection conditions may depend on the integration position modulating its level of expression and on the consequences of the particular anti-estrogen on the biology of the ZR-75-1 cells. Our observations that the mechanisms underlying resistance against diverse anti-estrogens differ are in line with previous observations in breast cancer cell models (Soulez & Parker 2001, Faridi et al 2003, Frasor et al 2004, Martin et al 2005, Fan et al 2006, Kuske et al 2006, Scafoglio et al 2006, Shaw et al 2006, Osipo et al 2007. Accordingly, patients with breast tumors failing on tamoxifen have been shown to respond to the pure anti-estrogen fulvestrant (Howell et al 2002, Osborne et al 2002, Howell 2006, indicating subtle differences in the underlying mechanisms of tumor growth control.…”
Section: Discussionsupporting
confidence: 92%
“…The probability of recovery of a particular gene under different selection conditions may depend on the integration position modulating its level of expression and on the consequences of the particular anti-estrogen on the biology of the ZR-75-1 cells. Our observations that the mechanisms underlying resistance against diverse anti-estrogens differ are in line with previous observations in breast cancer cell models (Soulez & Parker 2001, Faridi et al 2003, Frasor et al 2004, Martin et al 2005, Fan et al 2006, Kuske et al 2006, Scafoglio et al 2006, Shaw et al 2006, Osipo et al 2007. Accordingly, patients with breast tumors failing on tamoxifen have been shown to respond to the pure anti-estrogen fulvestrant (Howell et al 2002, Osborne et al 2002, Howell 2006, indicating subtle differences in the underlying mechanisms of tumor growth control.…”
Section: Discussionsupporting
confidence: 92%
“…MCF-7-LTED, the estrogen-hypersensitive MCF-7 subline, was generated from MCF-7 cells by long-term culture under estrogen-deprived conditions and thus they are called LTED cells (14) (a kind gift from Richard Santen). LTED cells are refractory to tamoxifen but sensitive to fulvestrant (11). MCF-7-TAMLT, long-term tamoxifen-stimulated tumors, were kindly provided by V. Craig Jordan and were developed by retransplanting growing estradiol-dependent MCF-7 tumors into new athymic mice and treating the mice with tamoxifen for >5 y (15).…”
Section: Methodsmentioning
confidence: 99%
“…A reduced need for estrogen by ER + cells is often linked to their resistance to TAM treatment (11). HOXB7 overexpression in MCF-7 cells resulted in a much reduced dependence on nutrients.…”
Section: Hoxb7 Expression Promotes Breastmentioning
confidence: 99%
“…However, in vascular endothelium, many studies have demonstrated the inhibition of ET-1 expression by estrogens [46,47], a mechanism that may explain the well-known vasoprotective estrogen effects [47].Fulvestrant in contrast to tamoxifen left gene expression of the ET system unaffected, supporting the perception of fulvestrant as the clinically superior compound. Different from the SERM tamoxifen, fulvestrant is an ER antagonist and ER downregulator without agonistic activity [48]. It is well-known that tamoxifen different from fulvestrant holds a considerable partial agonistic activity (PAA) on the ER [48,49], which easily explains the inducing effect of tamoxifen on the ET system, as the physiological ER agonist E 2 too enhanced gene expression of ET-1,…”
Section: Discussionmentioning
confidence: 99%
“…Different from the SERM tamoxifen, fulvestrant is an ER antagonist and ER downregulator without agonistic activity [48]. It is well-known that tamoxifen different from fulvestrant holds a considerable partial agonistic activity (PAA) on the ER [48,49], which easily explains the inducing effect of tamoxifen on the ET system, as the physiological ER agonist E 2 too enhanced gene expression of ET-1,…”
Section: Discussionmentioning
confidence: 99%